Asuhan Keperawatan Gangguan Integritas Kulit pada NY.K dengan Ulkus Dekubitus di Iryou Houlin Aiwa Kai Kaigo Roujin Hokken Shisetsu Ikeda En Jepang - Kavita Dwi Pramudya; Atun Raudotul Ma’rifah; Siti Haniyah (Jurnal Ilmiah Wahana Pendidikan, 2026)
This case study report highlights the issue of pressure ulcers, which pose a significant challenge in nursing care, especially for elderly people with limited mobility. At the Iryou Houlin Aiwa Kai Kaigo Roujin Hoken Shisetsu Ikeda En facility in Japan, approximately 30% of the elderly population suffer from pressure sores caused by prolonged pressure that inhibits blood flow and causes tissue damage. This study aims to describe comprehensive nursing care for patients with skin integrity disorders, from assessment to evaluation. Through a case study method on Mrs. K (72 years old) with a medical diagnosis of ischemic stroke, a pressure ulcer measuring ±4x3 cm was found in the sacrum area, accompanied by necrotic tissue, serous exudate, and pain.The main nursing diagnosis established was skin integrity impairment related to prolonged pressure. The interventions implemented included aseptic wound care and repositioning every two hours to distribute pressure on the body. After three days of treatment, the evaluation results showed improvement in tissue integrity, marked by reduced pain and improved granulation, although the wound had not yet completely closed. This study concluded that consistency in wound care and repositioning scheduling is crucial to prevent worsening of pressure ulcer conditions in long-term bedridden patients.